MAKING A SMALL TOWN LIVABLE:: PROMOTING SUSTAINABILITY THROUGH A NEW URBANIST APPROACH IN MEBANE, NORTH CAROLINA - Rifki, Fatih A.; Toker, Umut; Toker, Zeynep (ARCC Conference Repository, 2019)
A contemporary nexus of urban development discussions is the concept of sustainability, which is often presented as a viable remedy to many of the contemporary urban ills, i.e., diminished livability that is mostly blamed on suburban sprawl. Not only large metropolitan areas experience sprawl. Numerous relatively small towns have also been undergoing this kind of spatial transformation as their cores are emptied in favor of suburbs. Town of Mebane, North Carolina, is one such small town. Today, downtown Mebane is home to manufacturing plants, retail stores, institutional buildings, and residences as well as empty lots and boarded-up buildings. Its architectural scale is still charming and its gridiron network of streets is capable of accommodating various modes of traffic although precedence is given to the car. Furthermore, some of the downtown buildings are worthy of consideration as historic landmarks, although many have been clad with metal panels, disguising their authenticity. This paper is a progress report on the first of three phases of an urban design actionresearch project on downtown Mebane, being undertaken by NC State University Architecture Faculty and Doctoral Students. The goal of the project is to generate sustainable urban development principles, guidelines and standards that promote urban livability. This phase involves an inventory of the town’s physical, social, environmental and economical resources with New Urbanist "lenses" to develop specific sustainable urban development goals for the town’s future and strategies to achieve these. In the subsequent phase of the project, proposals will be developed with citizens’ input through citizens’ charettes. It is envisioned that the process and the consequent proposal developed for Mebane is presented as a model to other small North Carolina towns that are striving to alleviate many of the ills of sprawl in the last phase of the project.